ANALISIS PENGARUH KOMPONEN JALAN TERHADAP CAPAIAN LAIK FUNGSI JALAN TOL (Studi Kasus: Ruas Jalan Tol Jakarta-Bogor-Ciawi) - Lukmanul Hakim (Jurnal Teknik Sipil, 2017)
Jagorawi toll roads have a length of 59 km that is largely untested road-worthy function. To reduce the  number  of  accidents  that  occur,  toll  road  needs  correct  and  accurate,  planning,  design, construction,  and  maintenance  of  the  road  is  good  and  right.  This  study  aims  to  road  component effect  to  road  toll  function  outcome  using  Structural  Equation  Modeling  (SEM)  with  the  help  of software AMOS version 21. Results of the analysis showed that components of the achievements of the achievements  worthy  function  accounted  by  69%.  The  contribution  of  each  component  of  the  road, namely;  (1)  the  geometric  path  by  29%;  (2)  the  structure  of  the  pavement  by  55%;  (3)  building  a complementary  road  by    33%;  (4)  the  use  of  road  sections  by  46%;  (5)  implementation  and management of road engineering by 35%, (6) road equipment related directly to road users by 36%; (7) road equipment that are not directly related to road users by 36%; and (8) road administration by 31 %.